Linear DNA Molecules of Rice Mitochondrial Genome - 郑佐华 汪训明 金津 谈家桢 (中国科学通报：英文版, 1994)
Mitochondrial genome of higher plant is relatively difficult to study because of its larger genome varying from 200 to 2500 kb and its complex genome organization and structure. The organization and structure can be studied mainly by two ways. One is pulsed-field gel electrophoresis (PFGE), such as PFGE analysis of